The Influence of Music and Learning Motivation to the Results of Learning the Productive Practice in Vocational High School Tourism Group - Elida, Elida (INVOTEC, 2018)
The purpose of the research is to analyze difference of the results of students learning the practice of productive, that is: learning strategy between with music and without music, student who has high motivation even hard with learning process of with music and without music. Interactions between learning strategy with student learn motivation by music. This research is experiment research with factorial 2x2 designs. Population student X grade Tata Boga major tourism group of vocational high school in West Sumatra. The sample is taken by multistage random sampling. The Data is analyzed descriptively and ANAVA two way analyzed and continued by Tukey test. The findings research shows that (1) the result of student learning the practice of productive group with learning music is higher than without learning music. (2) there is interaction between processes using music with student motivation learning that giving difference influence to the productive practice student learning (3) the result of group of students learning the practice of productive who have high motivation by learning music is higher than without learning music, and (4) The result of a group of students learning the practice of productive who have low motivation with learning music is lower than without music.